(untitled) (LACCEI, 2024)
The purpose of this paper is to stablish a methodology of measuring and analysis efficiency in the administrative management, in the context of intermediate education (high schools), of school districts and zones in Ecuador. First, we did a literature revision about some models to evaluate the efficiency and analyze the advantages and disadvantages to each one. In this case we use a data envelopment analysis (DEA) considering the school districts as decision making unit (DMU). The pure technical efficiency (PTE) was estimated with three inputs (students, teachers, and budget) and three outputs (global index of approve “Ser Bachiller” test, retention rate and students approve test by subject) for each one 140 dmu’s. The data was obtained of the Ministry of education and corresponding to 2015. The results suggest that in general the districts are efficient (PTE average> 0.5 in all models) "producing" global index of approve “Ser Bachiller” test and retention rate, but the variation in the PTE of global index is bigger than PTE in retention rate case. Moreover, we can see that the most school districts efficient are in two specific zones, zone 8 (Guayaquil, Samborondón, Durán) and zone 9 (Metropolitan district of Quito). Finally, a sensibility analysis suggests that the number of students in each school district (input 1) is not a significant input in estimation of technical efficient coefficients in DEA model. These results obtained provide interesting points for educational policy discussion in Ecuador.